Something silver, something blue (big book) - Drew, David (Nelson Australia South Melbourne, 1994)
"Something Silver, Something Blue" is a heartwarming story that often revolves around themes of love, friendship, and the journey toward a significant life event, typically a wedding. The narrative typically follows characters as they navigate relationships, experiences, and emotions leading up to this special occasion. Throughout the story, elements of tradition and the symbolism behind "something old, something new, something borrowed, and something blue" are explored. The characters may learn important lessons about commitment, support, and the significance of cherished memories. With a blend of heartfelt moments and lighthearted interactions, the book captures the essence of love and celebration, making it a delightful read for those interested in romance and family dynamics.